2011
DOI: 10.1002/smi.1374
|View full text |Cite
|
Sign up to set email alerts
|

Work–home interference and the relationship with job characteristics and well‐being: a South African study among employees in the construction industry

Abstract: Although the relationship between job characteristics, work–home interference (WHI) and work‐related well‐being has been researched in Western societies, this relationship has not often been tested in non‐Western societies such as South Africa and among low‐wage non‐professional workers, like construction workers. The aim of this study was to test the mediating effect of negative and positive WHI in the relationship between job characteristics (job demands and job resources) and work‐related well‐being (burnou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0
5

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 90 publications
(168 reference statements)
1
27
0
5
Order By: Relevance
“…Work–home interference is defined as situations in which negative or positive stress reactions at work influence a person’s function at home; this is more common than home–work interference in which stresses of home influence performance at work [38]. Young workers, both women and men, may have a greater wish or need than older workers to separate their work and their private lives, possibly because this age group may value individualism more highly.…”
Section: Discussionmentioning
confidence: 99%
“…Work–home interference is defined as situations in which negative or positive stress reactions at work influence a person’s function at home; this is more common than home–work interference in which stresses of home influence performance at work [38]. Young workers, both women and men, may have a greater wish or need than older workers to separate their work and their private lives, possibly because this age group may value individualism more highly.…”
Section: Discussionmentioning
confidence: 99%
“…Por contra, la falta de datos referidos a otras variables susceptibles de afectar al síndrome que permitan confirmar su efecto en árbitros, así como la falta de información sobre el sueldo percibido, el cual se entiende como un importante amortiguador psicológico que podría reducir los efectos emocionales (Mostert, Peeters, & Rost, 2011), suponen las principales limitaciones.…”
Section: Discusión Y Conclusionesunclassified
“…Although family responsibilities are often regarded by employees as one of the top demands leading to work stress (Bakker, Ten Brummelhuis, Prins & Van der Heijden, 2011), work can also energise people and contribute to experiences of psychological meaningfulness, competence and availability to work, and personal engagement. Previous research showed that work-home and home-work interaction affect the engagement of employees (Bakker et al, 2011;Lingard, Brown, Bradley, Bailey & Townsend, 2007;Mostert, Cronjé & Pienaar, 2006;Mostert, Peeters & Rost, 2011). Two psychological conditions, namely psychological meaningfulness and psychological availability, seem relevant for transferring the effects of work-home/home-work interaction to employee engagement (Kahn, 1990;Kahn & Heapy, 2014;May et al, 2004).…”
Section: Introductionmentioning
confidence: 99%